Exploring the managing of flood disaster: a Malaysian perspective - Izham Mohamad Yusoff,; Aznarahayu Ramli,; Nurul Azni Mhd Alkasirah,; Norashila Mohd Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Flooding occurs periodically in Malaysia and has become a common occurrence. This annual occurrence of floods has given a big impact on lives of humans and other living being. Due to the negative impact of floods, we need to pay serious attention and take an alternatives way to reduce this disaster. This paper reviews previous articles relating to flood disaster management in Malaysia based on electronic databases which are subscribed by the university library. The flood disaster management in Malaysia involves four phases, which are prevention/mitigation, preparedness, response and recovery. The disaster prevention/mitigation and preparedness are the best way forward because if these two phases were successfully handled, the burden of the next phases will be reduced. Besides, the agencies responsible for the management of floods in Malaysia have been identified in this study. The usage of technology for managing flood events has also been reviewed. The role of communities affected by the floods is no less important. Their awareness and readiness in facing the flood disaster are indispensable so that the negative impacts resulted from the disasters can be minimised. Therefore, the community should be educated to improve their awareness regarding flood management especially on how and what to prepare for flood as well as how to react during the flood.